Financial Performance and Bankruptcy Risk at Bank Muamalat - Siti Ena Aisyah Simbolon (Business Finence Analyst Co.,, 2023)
This study aims to see the effect of financial performance represented by the variables CAR, FDR and ROA on the risk of bankruptcy of PT Bank Muamalat Indonesia with the Altman Z-score method. The data used is the financial statements of 2014-2018. It was found that CAR, FDR and ROA had no effect on bankruptcy risk.